CONVERSION OF AGRICULTURAL SECTOR INTO MANUFACTURING SECTOR IN ACEH PROVINCE - Yasrizal Yasrizal; Muliadi Muliadi; Damrus Damrus (Sensei International Journal of Education and Linguistic, 2022)
The change in labor structure and quality from the agricultural sector to the industrial sector has created prospects for expanded job opportunities, which are much more important year-on-year in comparison with the agricultural sector. Moreover, the manufacturing sector also offers resources for its employees to boost their health. The workforce experienced an average annual decrease of -1.69 percent from 1994 to 2017, but the manufacturing sector experienced a 6.44 percent rise in jobs. This thesis is a secondary study using time series data collected from the Aceh Province Central Statistical Agency (BPS). The model is structured in the form of simultaneous equations consisting of 6 structural equations and 2 identity equations. The model is an Econometrics model that is used to classify the variables affecting the movement of labor to the manufacturing sector in the agricultural sector. The results of the study indicate that salaries in the industrial sector are higher than wages in the agricultural sector, which is what encourages workers in the agricultural sector to tend to migrate to the industrial sector (transformation). The industrial sector consumes more labor than the agricultural sector with every rise in the number of industries in Aceh Province. Seen by the growth of 1 Aceh industrial unit capable of employing hundreds of employees.